The bisphosphonate, zoledronic acid, induces apoptosis of breast cancer cells: evidence for synergy with paclitaxel. - Jagdev, S; Coleman, R; Shipman, C; Rostami-H, A; Croucher, P (2001)
Bisphosphonates are well established in the management of breast-cancer-induced bone disease. Recent studies have suggested that these compounds are effective in preventing the development of bone metastases. However, it is unclear whether this reflects an indirect effect via an inhibition of bone resorption or a direct anti-tumour effect. The breast cancer cell lines, MCF-7 and MDA-MB-231 cells were treated with increasing concentrations of the bisphosphonate, zoledronic acid, for varying time periods, in the presence or absence of paclitaxel. The effects of zoledronic acid were determined by assessing cell number and rate of apoptosis by evaluating changes in nuclear morphology and using a fluorescence nick translation assay. Zoledronic acid caused a dose- and time-dependent decrease in cell number (P< 0.001) and a concomitant increase in tumour cell apoptosis (P< 0.005). Short-term exposure to zoledronic acid was sufficient to cause a significant reduction in cell number and increase in apoptosis (P< 0.05). These effects could be prevented by incubation with geranyl geraniol, suggesting that zoledronic acid-induced apoptosis is mediated by inhibiting the mevalonate pathway. Treatment with zoledronic acid and clinically achievable concentrations of paclitaxel resulted in a 4-5-fold increase in tumour cell apoptosis (P< 0.02). Isobologram analysis revealed synergistic effects on tumour cell number and apoptosis when zoledronic acid and paclitaxel were combined. Short-term treatment with zoledronic acid, which closely resembles the clinical setting, has a clear anti-tumour effect on breast cancer cells. Importantly, the commonly used anti-neoplastic agent, paclitaxel, potentiates the anti-tumour effects of zoledronic acid. These data suggest that, in addition to inhibiting bone resorption, zoledronic acid has a direct anti-tumour activity on breast cancer cells in vitro.